Development of Inhibitive Enzyme Assay for Heavy Metal Detection Using Phosphomolybdo-Reductase Produce by Bacillus Sp. Isolate A. rzi - Othman, Ahmad Razi (2010)
The department of Environmental Malaysia in 2006 recorded that heavy metals were recorded at levels above the Maximum Permissible Limit at various places in Malaysia. Bioassays using enzyme and microorganism were currently in placed as these methods gave faster results and are cheaper compare to instrumental technology. This research is based on an inhibitive enzyme-based bioassay to detect heavy metals in soil and water sample using heavy metals sensitive bacteria. About 106 single colonies were isolated and assayed for molybdenum blue quantification using Low Phosphate Media agar (LPM). A colony isolated from Pulau Pangkor labeled as P2 (2) exhibited the lowest Mo-reducing activity in the presence of heavy metals and was selected for further studies. This bacterium is identified as Bacillus sp. isolate A.rzi based on the carbon utilization profiles using Biolog GP plate and partial 16S rDNA molecular phylogeny. The sequence of the 16s rRNA of the bacterium has been submitted to genbank with the accession no EU835195. Optimizations studies carried out for this bacterium showed that maximum temperature and pH supporting molybdate reduction were room temperature and pH 6.0, respectively. The absorption spectrum of the molybdenum blue product showed a maximum peak at 865 nm and a shoulder at 700 nm indicating the involvement of a phosphomolybdate intermediate. Different electron donors such as glucose, sucrose, maltose, mannose, mannitol, lactose, starch, glycerol, tartarate, formate and acetate supported molybdate reduction except citrate. Molybdate reduction to Mo-blue was found to increase as molybdate concentration was raised from 0 to 50 mM and is inhibited at higher molybdate concentrations. The optimum phosphate concentration for molybdate reduction for this bacterium when molybdate concentration was fixed at 50 mM was 3 mM. Partial purification using MonoQ anion exchange chromatography showed that enzyme activity was eluted at tubes numbered between 20 and 23. Almost two fold purification was achieved after chromatography. A plot of initial rates against NADH concentrations at 10 mM LPPM registered an apparent Vmax for NADH at 79.72 nmole Mo blue/min/mg protein and a Km of 19.3 mM while the plot of initial rates against LPPM concentrations at 30 mM NADH (saturating) registered a Vmax for LPPMH at 89.1 nmole Mo blue/min/mg protein and a Km of 6.26 mM. Screening of inhibition by metals was also carried out, and the results showed that reduction was inhibited by copper, mercury and lead. The calculated IC50 value for copper, mercury and lead were 0.2476 mg/L, 0.3543 mg/L and 0.4875 mg/L, respectively. Field trial works using the assay showed that the most polluted samples came from Sg. Derhaka Juru, Juru, Penang, and Bukit Juntong, Bentong, Pahang which exhibited nearly 100% inhibition of enzyme activity and was corroborated by ICP analysis. Another sample from Kg. Ladang showed small amount of copper but not enough to show inhibition of the enzyme activity. Waters from clean areas and tap water all showed no inhibition to the enzyme activity and data were corroborated with ICP analysis. In general, all of the objectives have been met. This study hopefully can contribute to this country in monitoring pollution since this newly developed bioassay is low in cost, easy to handle compared to conventional methods and enable real time results.